Avaliação do comportamento mecânico das argamassas de revestimento com a substituição parcial do cimento por pó de vidro como material pozolânico - Gomes, Fredson Alan (Universidade Federal Rural do Semi-Árido, 2019)
The preservation of the environment and sustainable growth in the construction industry means that the students of the Universities and Technological Centers are looking for procedures and implements to obtain alternative materials that allow the use of the most varied types of waste from the construction sites. It is known that in civil construction, lately, the question of the reuse and reuse of the raw materials and products used in the works has been a concern for the engineers and researchers of the area, seeking a balance on the consumption of these raw materials and its vast generation of residue. Glass is one of the building materials that has presented a high consumption in the current days, generating a lot of waste in landfills and dumps. In this context, the present work seeks to provide a technical way to replace part of the cement by pozzolanic material, in this case, ordinary glass powder from glass scrap waste. The possibility was evaluated by the comparison of results of mechanical tests on fresh and hardened coating mortar specimens ruptured at 28 days. Two traces were used: a 1: 1: 4 trace, cement, lime and fine sand (standard) and another with the same trace, replacing 25% of the cement with ordinary glass powder. Mortars are materials of considerable use in constructions in the most diverse stages, being usually used for laying of masonry, coating of walls and regularization of floors and subfloors. It was observed that the common glass residues studied in this work presented a good potential and alternative for the use as pozzolanic material in cement mixtures in coating mortars, being it clarified that for works in which the mechanical properties are not so preponderant, this pozzolanic material can be used, since the compressive strength around 7 to 10 MPa and for flexural tensile strength of 2 to 4 MPa is something to be considered for use in coating mortar, works that wish to obtain certifications regarding the preservation of the environment.
Monografia
Keywords: Argamassas de revestimento; Propriedades mecânicas; Pó de vidro; Construção civil; ENGENHARIAS::ENGENHARIA CIVIL